2021
DOI: 10.1093/mnras/stab549
|View full text |Cite
|
Sign up to set email alerts
|

The quasar feedback survey: discovering hidden Radio-AGN and their connection to the host galaxy ionized gas

Abstract: We present the first results from the Quasar Feedback Survey, a sample of 42 z < 0.2, [O iii] luminous AGN (L[O III] > 1042.1 ergs s−1) with moderate radio luminosities (i.e. L1.4GHz > 1023.4 W Hz−1; median L1.4GHz = 5.9 × 1023 W Hz−1). Using high spatial resolution (∼0.3–1 arcsec), 1.5–6 GHz radio images from the Very Large Array, we find that 67 percent of the sample have spatially extended radio features, on ∼1–60 kpc scales. The radio sizes and morphologies suggest that these may be lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 183 publications
(260 reference statements)
3
38
2
Order By: Relevance
“…Such nuclei are part of a large population of radio LLAGN and faint nuclear starbursts ( 10 17.6 W Hz −1 ). This result adds observational evidence that a large fraction of LLAGN (even RQ AGN) feature low-power galactic-scale jets (Webster et al 2021), which may have a tremendous impact on their hosts by continuously injecting energy, a fundamental ingredient for galaxy feedback (Morganti 2017;Jarvis et al 2019;Hardcastle & Croston 2020;Smith et al 2020b;Jarvis et al 2021;Venturi et al 2021), as supported by the state-of-the-art jet simulations (Massaglia et al 2016;Mukherjee et al 2018Mukherjee et al , 2020.…”
Section: The Lemmings Viewsupporting
confidence: 63%
“…Such nuclei are part of a large population of radio LLAGN and faint nuclear starbursts ( 10 17.6 W Hz −1 ). This result adds observational evidence that a large fraction of LLAGN (even RQ AGN) feature low-power galactic-scale jets (Webster et al 2021), which may have a tremendous impact on their hosts by continuously injecting energy, a fundamental ingredient for galaxy feedback (Morganti 2017;Jarvis et al 2019;Hardcastle & Croston 2020;Smith et al 2020b;Jarvis et al 2021;Venturi et al 2021), as supported by the state-of-the-art jet simulations (Massaglia et al 2016;Mukherjee et al 2018Mukherjee et al , 2020.…”
Section: The Lemmings Viewsupporting
confidence: 63%
“…A similar correlation has also been observed in radio-quiet sources using SDSS-measured [OIII] luminosities (Jarvis et al 2021). Here we investigate whether similar correlation exists in red geyser galaxies.…”
Section: Integrated Propertiessupporting
confidence: 79%
“…As reported in §5.1, 14 out of 28 (∼ 50%) sources showing resolved radio emission in LOFAR observations display a compact radio morphology. Although similar radio-quiet compact sources hosting radio AGN have been observed to host small-scale (∼ 1 kpc) radio jets in higher spatial resolution (< 1 ) radio observations in previous studies (Jarvis et al 2019(Jarvis et al , 2021Venturi et al 2021;Panessa et al 2019;Webster et al 2021), the presence of resolved radio jets in the red geyser sample is observed to be quite rare with the current 5 resolution.…”
Section: Integrated Propertiesmentioning
confidence: 54%
See 2 more Smart Citations